Trade in agri-food products: Perspectives from bibliometric analysis - Andreea Daniela Giucă (Agrarian Economy and Rural Development - Trends and Challenges. International Symposium. 14th Edition, 2023)
Growing global population and growing demand for food have put a lot of pressure on the global food supply chain. The global population is expected to reach 8.5 billion by 2030 and 9.7 billion by 2050. In this context, providing agri-food products in the quantity needed by an ever-growing population puts even greater pressure on the supply chain with agro-food products globally. The present study aims to identify research trends in the field, so that it can identify the characteristics of trade in agri-food products. These are illustrated through a bibliometric study where the research contributions of authors, countries and scientific journals are presented. By using this research method, we want to identify the links between the number of documents published in the field, the research topic, the frequency of citation of the articles and the interest given to the research subject depending on the country.
Keywords: Q10; Q13; Q17; 330; trade; agro-food products; trade balance; supply chain; bibliometric analysis